2013
DOI: 10.1515/hf-2012-0185
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of xylan to the brightness development and stability in the final ECF bleaching of eucalypt (Eucalyptus globulus Labill.) kraft pulp

Abstract: under the same conditions as pulps in a final bleaching stage and were further characterized. 1 H nuclear magnetic resonance, size exclusion chromatography, UV-vis spectroscopy in cadoxen solution, and UV-resonance Raman spectroscopy were applied as analytical methods. The final ClO 2 stage generated new unsaturated moieties in xylan, whereas H 2 O 2 was very effective in the removal of xylan-related chromophores. The role of xylan to the delay of brightness development in the final ClO 2 stage was highlighted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Lignin residues, carbonyl groups, xylan, hexenuronic acid (HexA) groups, and transition metal ions are involved in the yellowing reactions1314. Residual lignin, the products of polysaccharide chain thermal decay and xylan are the main (although debatable) causes for heat-induced yellowing of chemical pulps15. Light-induced yellowing is principally associated with lignin-rich pulps (i.e., HYP).…”
mentioning
confidence: 99%
“…Lignin residues, carbonyl groups, xylan, hexenuronic acid (HexA) groups, and transition metal ions are involved in the yellowing reactions1314. Residual lignin, the products of polysaccharide chain thermal decay and xylan are the main (although debatable) causes for heat-induced yellowing of chemical pulps15. Light-induced yellowing is principally associated with lignin-rich pulps (i.e., HYP).…”
mentioning
confidence: 99%
“…However, in the DEDXD sequence, for the same chlorine dioxide load in the final D stage, higher brightness and lower reversion were achieved, when compared with the DEDD sequence. Interference of xylanase with structures responsible for the pulp color and brightness reversion may be inferred . The extraction of stabilised quinones chromophoric structures has been mentioned as a result of the xylanase treatment .…”
Section: Resultsmentioning
confidence: 99%
“…Recently it was found that a final D stage in the DEDD sequence caused new unsaturated structures in xylan, which were much less abundant in pulp bleached by a final P stage in the DEDP sequence . The important role of xylan as a source of chromophores and their effect on brightness development and stability of bleached eucalypt pulps have been evidenced . Xylan in eucalypt kraft pulp is structurally associated with residual lignin, which is the main source of chromophore structures .…”
Section: Introductionmentioning
confidence: 99%
“…Taking into account the fact that all materials presented similar lignin contents (between 1.2% and 1.6%), the high brightness of the E-MFC film could be related to its lower xylan content (19.1%). In addition, xylan-lignin complexes are a source of residual poly-conjugates chromophores [51].…”
Section: Optical and Mechanical Propertiesmentioning
confidence: 99%